Gestão urbana e política habitacional: qualidade ou quantidade?: a trajetória da Companhia Urbanizadora de Belo Horizonte - Henrique de Queiroz Coelho (2002)
The urbanizing process of Brazilian cities has shown through the last years the so called informal cities, in a context of demands that include a significant part of the population. This has emphasized the local public authority role, usually associated, in a good part of the cases, to a methodology that aims the optimization of results, in a perspective thattries to balance the quantitative/or material resources and strategy guidelines. In this argumentation line, this work analyses the recent trajectory of the Companhia Urbanizadora de Belo Horizonte (Urbel), when introducing a public policy of housing composed of programs and projects that are based on the articulation with the population.Developed from a documentary data research and semi-structured interviews with managers and technicians connected to the process and chosen according to the representation of their function in the shaping of the introduced proposal, this work has noticed that, keeping in mind the natural difficulties that the historical housing deficit generates, Urbel tried to structure a performance where the political, administrative andtechnical dimensions were present, enlarging the comprehension of the housing issue and giving it a more substantial and qualitative connotation. This situation, if shows the progress in the construction of a comprehensive housing perspective, with popular participation and evolvement, also finds difficulties concerning the direct action ofpunctual nature, associated to the lack of houses and the non-meeting of the immediate demand.